2020
DOI: 10.3390/ijerph17144966
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Dyadic Pain Management Program for Community-Dwelling Older Adults with Chronic Pain: A Pilot Randomized Controlled Trial

Abstract: Background: Chronic pain is a major health problem among older adults and their informal caregivers, which has negative effects on their physical and psychological status. The dyadic pain management program (DPMP) is provided to community-dwelling older adults and informal caregivers to help the dyads reduce pain symptoms, improve the quality of life, develop good exercise habits, as well as cope and break the vicious circle of pain. Methods: A pilot randomized controlled trial was designed and all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 73 publications
(82 reference statements)
0
12
0
Order By: Relevance
“…Therefore, the innovative, effective and feasible intervention methods should be considered. Evidence identified that internet interventions can include more tailored information, approach larger research population, and supply more anonymity than face-to-face traditional interventions [ 17 , 18 , 19 , 20 , 21 ]. In 2020, China News reported that the internet by a device of mobile or computer was available to 61% of the Chinese population [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the innovative, effective and feasible intervention methods should be considered. Evidence identified that internet interventions can include more tailored information, approach larger research population, and supply more anonymity than face-to-face traditional interventions [ 17 , 18 , 19 , 20 , 21 ]. In 2020, China News reported that the internet by a device of mobile or computer was available to 61% of the Chinese population [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…3 It is well established that persistent pain can lead to negative physical and psychological effects, including decreased quality of life. 4 Further,…”
mentioning
confidence: 95%
“…3 It is well established that persistent pain can lead to negative physical and psychological effects, including decreased quality of life. 4 Further, pain contributes to decreases in paid work, increases in disability benefits, and healthcare and treatment costs of over an estimated $635 billion a year. 5 Without intervention or effective treatment, persistent pain can result in increasingly adverse outcomes for the individual such as falls, immobility, depression, or social isolation, 4 and greater financial and caregiving burden placed on families.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The steps, intensity and appropriateness for older adults were reviewed by the physiotherapist. The effectiveness of exercise guidebook was validated in a pilot randomized controlled trial involving 64 community‐dwelling older adults with chronic pain (Li et al, 2020). The present study tested the effectiveness of a MMEP.…”
Section: Introductionmentioning
confidence: 99%